1999
DOI: 10.1136/gut.45.4.489
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic regression of Barrett's oesophagus during omeprazole treatment; a randomised double blind study

Abstract: Background-Barrett's oesophagus, columnar metaplasia of the epithelium, is a premalignant condition with a 50-100-fold increased risk of cancer. The condition is caused by chronic gastro-oesophageal reflux. Regression of metaplasia may decrease the cancer risk. Aims-To determine whether elimination of acid gastro-oesophageal reflux induces a regression of metaplastic epithelium. Methods-Sixty eight patients with acid reflux and proven Barrett's oesophagus were included in a prospective, randomised, double blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
139
2
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(153 citation statements)
references
References 17 publications
4
139
2
8
Order By: Relevance
“…9 Recent studies suggested a small but measurable decrease in the length of BE in patients treated with high-dose proton-pump inhibitor therapy. [10][11][12][13] However, no study has examined the effect of antisecretory therapy prior to the diagnosis of BE on the length of Barrett's segments in gastro-oesophageal reflux disease (GERD) patients with newly diagnosed BE. At the Southern Arizona Department of the Veterans Affairs (VA) Healthcare System, a single experienced endoscopist has been responsible for performing endoscopy and collecting information on prior therapy on newly referred patients with diagnosed or suspected BE over the past 20 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Recent studies suggested a small but measurable decrease in the length of BE in patients treated with high-dose proton-pump inhibitor therapy. [10][11][12][13] However, no study has examined the effect of antisecretory therapy prior to the diagnosis of BE on the length of Barrett's segments in gastro-oesophageal reflux disease (GERD) patients with newly diagnosed BE. At the Southern Arizona Department of the Veterans Affairs (VA) Healthcare System, a single experienced endoscopist has been responsible for performing endoscopy and collecting information on prior therapy on newly referred patients with diagnosed or suspected BE over the past 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16]. Of all patients, 139 (41%) had prior use of histamine-2 receptor antagonists, or proton-pump inhibitors (41 used both), and 201 (59%) used neither prior to the diagnosis of Barrett's oesophagus.…”
mentioning
confidence: 99%
“…There is published evidence that Barrett's esophagus can regress, even completely, under PPI use. However the complete circular distal squamous reepithelization of long segments of Barrett's esophagus has not been described in any of the published trials on the subject (19,20).…”
Section: First Recognized In the 19mentioning
confidence: 99%
“…These results thus indicate that anti-reflux surgery in patients with BE does not prevent the development of EAC appreciably more than medical therapy. There is some evidence to suggest that PPIs can lead to a partial regression of BE [121,122] and delay the progression to dysplasia or EAC [123,124]. Accordingly, the increasing use of PPIs since the late 1980s might have contributed to the slight drop in the incidence of EAC over the past several decades.…”
Section: Neoplastic Preventionmentioning
confidence: 99%
“…Accordingly, the increasing use of PPIs since the late 1980s might have contributed to the slight drop in the incidence of EAC over the past several decades. Moreover, since the 1990s, several studies using varying doses of PPIs reported partial regression or the development of squamous islands [121,[125][126][127][128], while circumferential regression of the columnarized segment was rare.…”
Section: Neoplastic Preventionmentioning
confidence: 99%